Mortality and health outcomes associated with non-communicable disease risk factors: Protocol for the IRAN-STEPS Follow-Up Cohort (ISFUC) based on the 2021 national survey - Hosein Ataei-Goujani; Sarmad Salehi; Pardis Zarepour; Ozra Tabatabaei-Malazy; Nazila Rezaei; Mina Mirzad; Anis Gharajeh; Samaneh Akbarpour; Yosra Azizpour (PLOS One, 2026)
Non-communicable diseases (NCDs) account for more than 81% of all deaths in Iran and impose a substantial burden on the national health system. Although Iran has implemented multiple initiatives, including the World Health Organization’s STEPwise Approach to NCD Risk Factor Surveillance (STEPS), to monitor NCD risk factors, critical gaps remain in longitudinal outcome assessment, particularly in the post–COVID-19 period, for which national data are limited. Moreover, in the context of declining fertility rates and demographic challenges in Iran, emerging evidence suggests that metabolic and lifestyle-related NCD risk factors are associated with impaired reproductive health, fertility potential, and childbearing behaviors. Therefore, the assessment of reproductive outcomes within population-based NCD surveillance frameworks addresses an important knowledge gap in Iran. The Iran STEPS Follow-Up Cohort (ISFUC) is established to evaluate mortality, health outcomes related to NCD risk factors, and fertility related outcomes using population-based data from the 2021 STEPS survey. The ISFUC is a population-based cohort study established through follow-up of participants from the nationally representative 2021 Iranian STEPS survey. The 2021 STEPS survey constitutes the baseline assessment, whereas ISFUC represents the subsequent follow-up phase. Baseline assessments were collected through interviewer-administered questionnaires, standardized physical measurements, and laboratory analyses of blood and urine biomarkers. Follow-up began in 4 April 2025, a five-years interval after baseline, and is ongoing. It will be conducted through structured telephone interviews by trained staff after renewed verbal consent. Study outcomes include all-cause mortality, healthcare utilization, injuries, reproductive health indicators, fertility-related behaviors and attitudes, and use of governmental childbearing support policies. Mortality outcomes are validated through linkage with the national death registry. Questionnaire validity was ensured using expert review, the Content Validity Ratio, and the Content Validity Index methods. By linking comprehensive 2021 STEPS baseline data with follow-up information on health, healthcare utilization, mortality, and reproductive outcomes, ISFUC provides a national platform for investigating Iran’s evolving epidemiological and demographic health challenges.